PENGARUH GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN DENGAN SUSTAINABLE DEVELOPMENT SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN INDEKS SRI-KEHATI TAHUN 2020–2024: THE EFFECT OF GREEN ACCOUNTING ON FINANCIAL PERFORMANCE WITH SUSTAINABLE DEVELOPMENT AS A MEDIATION VARIABLE IN SRI-KEHATI INDEX COMPANIES IN 2020–2024 - Marjuki, Muhamad; Rachman, Andry Arifian (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the effect of green accounting on financial performance with sustainable development as a mediating variable. This research adopts a quantitative approach using Partial Least Squares (PLS) analysis with SmartPLS 4 software. The sample consists is companies listed on the SRI-KEHATI Index during the 2020–2024 period, selected through purposive sampling. The findings indicate that green accounting has a positive and significant effect on financial performance. However, green accounting has a negative and insignificant effect on sustainable development. Sustainable development, on the other hand, has a minor but favorable impact on financial performance. Furthermore, sustainable development is unable to mediate the relationship between green accounting and financial performance.